P= 1+x+x^2+…+x^10. chứng minh rằng xP – P=x^11-1

Question

P= 1+x+x^2+…+x^10. chứng minh rằng xP – P=x^11-1

in progress 0
Hailey 1 tháng 2021-08-31T17:14:00+00:00 2 Answers 4 views 0

Answers ( )

    0
    2021-08-31T17:15:06+00:00

    Đáp án:

     

    Giải thích các bước giải:

     $P=1+x+x^{2}+x^{3}+…+x^{10}$

    $⇔xP=x+x^{2}+x^{3}+…+x^{11}$

    $⇔xP-P=(x+x^{2}+x^{3}+…+x^{11})-(1+x+x^{2}+x^{3}+…+x^{10})$

    $⇔xP-P=x^{11}-1$  (đpcm)

    0
    2021-08-31T17:15:44+00:00

    Ta có:

    $P = 1 + x + x^2 + … + x^{10}$

    $⇔ xP = x . (1 + x + x^2 + … + x^{10})$

    $⇔ xP = x + x^2 + x^3 + …. + x^{11}$

    $⇔ xP – P  = ( x + x^2 + x^3 + …. + x^{11}) – (1 + x + x^2 + … + x^{10})$

    $⇔ xP – P = x^{11} -1$($đpcm$)

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )